The elastic field of a wedge disclination in a radially graded cylinder - Tan, Darrin Yan Zhi (Nanyang Technological University, 2022)
The integration of disclination densities [1] by deWit [2] has solved the standard solutions for disclination in an indefinitely long elastic circular cylinder. The displacement and stress fields of a wedge disclination in a radially graded cylinder are studied in this work. The method is to solve the equilibrium equations directly in the radial direction. The cylinder's material gradient is assumed to follow a power law, which is represented by a gradient index. The aim of this project is to derive a new Lamé constant formula using the First Order solution and compare it with the classical solution to highlight the differences between the results.